Spirituality and Trauma: The Role of Clergy in the Treatment of Posttraumatic Stress Disorder - Sigmund, Judith A. (Journal of religion and health, 2003)
An increased awareness of the spiritual aspects of health and illness has recently led to changes in psychiatry residency training as well as hospital accreditation requirements. The spiritual impact of trauma has been an area of particular interest, as trauma evokes certain existential questions and crises. It is estimated that from 5-11% of trauma survivors will go on to develop posttraumatic stress disorder (PTSD). Given the spiritual challenges of the experience of trauma, patients with PTSD could benefit from spiritual assessment and intervention as part of their overall treatment plan, and clergy can be utilized to perform this. The literature exploring the spiritual impact of trauma and the use of clergy in the treatment of trauma survivors is reviewed. The methods used by three chaplains in a residential treatment program for PTSD at one facility are described and discussed. Both the literature and the experiences of the clergy suggest that exploration of trauma-related existential conflicts in patients with PTSD is beneficial. However, there is a notable dearth of controlled scientific studies evaluating the effectiveness of spiritual interventions with this treatment population. The need for controlled studies to verify the usefulness of spiritual assessment and intervention in patients with PTSD is noted, and a more rigorous analysis of how clergy can best serve this treatment population is encouraged.